When end of treatment situations challenge patient-centered care: a discussion paper proposing new theoretical insights - Bonazza, Federica; Lamiani, Giulia; Borghi, Lidia; Del Negro, Silvia; Leone, Daniela; Vegni, Elena (Frontiers in Psychology, 2024)
Introduction According to the Institute of Medicine patient-centered medicine is one of the six crucial dimensions of health care quality. Although the patient-centered care model is widely recognized for its ethical underpinnings and effectiveness, its practical implementation still raises challenges, especially in end-of-treatment situations. This discussion paper offers an overview of the challenges facing the physician-patient relationship in end-of-treatment situations. Methods We developed three clinical vignettes and made some theoretical considerations about ethical issues related to the decision-making process leading to the end of treatment. Results We identified two main challenges that end-of-treatment situations pose to patient-centered care: (1) when the patient’s autonomy challenges the best clinical treatment; and (2) when the proposed treatment (discontinuation of treatment) challenges the patient’s preferences. Discussions Patient-centered care supports personalized decision-making, in which the physician’s approach varies according to the patient’s situation and individuality. The idea of beneficence may change during care, because of acceptance of the patient’s principles or a change in the primary goal of care.